138P Prognostic implications of residual disease tumour-infiltrating lymphocytes in gastric cancer patients after neoadjuvant chemotherapy. (15th December 2019) - Xing, X; Jia, S; Feng, Y; Zhang, M; Ji, J
Abstract: Background: We have reported higher density of tumour-infiltrating lymphocytes (TILs) and PDL1 expression correlated with better outcome in treatment naive gastric cancer patients. Here the prognostic value of residual disease (RD) TILs and PDL1 expression is further evaluated. Methods: Immunohistochemistry was performed on a tissue microarray including 310 neoadjuvant chemotherapy GC specimens using PD1, PDL1 and PDL2 antibodies. T cell markers CD3 and CD8 were also stained and quantified by automated image analysis. Results: The median age was 58.5 years (range: 22–89 years). There was a positive correlation between TIL level and PDL1 expression. 37.8% of the cases showed membranous PD-L1 expression in tumor cells and 74.9% in infiltrating immune cells. PDL1 expression rate was rather higher in poorly differentiated samples and in patients without metastasis. CD8+ and CD3+ T cell densities were significantly lower with increasing post-NAC tumor size. CD8+ T dell density was also negatively correlated with tumor invasion level and lymph node metastasis. CD3+ and CD8+ T cell densities were significantly associated with improved OS, although only CD8+ T cell density remained a significant predictor in multivariate analysis [HR:0.974(95%CI:0.954-0.994), P = 0.013]. Conclusion: High CD8+ T cell density is closely related with late tumor stage, and significantly predicts improved overall survival in gastric cancer patients after neoadjuvant chemotherapy. Legal entity responsible for the study: Jiafu Ji. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.